Deviation among Ghanaian Basic School Pupils Use of English in the Classroom: A Case Study of Bono and Ahafo Regions - Glover-Quartey, Lilian; Yamoah, Kofi Kyei (FOSTER: Journal of English Language Teaching, 2023)
The focus of this study is to discuss some deviations and innovations basic school pupils in the Bono and Ahafo regions of Ghana use in their classrooms and how these deviations are applied to their communication in the classroom. A descriptive survey design was adopted to help achieve these objectives. A qualitative approach was adopted to help explain the study better. A total population of 9,219 pupils and a sample size of 400 pupils were observed for the study. The findings of the study revealed that in the area of phonology, pupils replace the inter-dental fricative /ð/ with a voiced alveolar stop /d/. They also used the voiceless dental fricative /θ/ in place of /t/ a voiceless alveolar in their speech. Again, most pupils also use the trill /r/ in place of the /l/ sound both in writing and articulation. Under semantics, pupils usually transliterate statements from their L1 into the target language (English) and tend to use hyperbole for emphasis. Furthermore, over-generalization of syntactic rules was found as one of the innovations pupils make in classroom communication. Spelling pronunciation was also found as part of the innovations basic school pupils use in classroom communication.